Fearbook club - Hamilton, Richard Ashley (Sherman Oaks, California Aftershock Comics, 2022)
"When shy 6th-grade shutterbug Whit Garcia starts middle school, he's forced to join a yearbook club with three other weirdos who will never be voted "most likely to succeed." But after the ghosts of missing students start haunting them, Whit, Hester, Hillary and Press must solve the supernatural secret behind these spirits - or their yearbook club will be voted most likely to join them. But are these ghostly students the real bad guys? Or are they just warning Whit and his friends? Warning them about a darkness beyond their schoolyard...a darkness that threatens to swallow the school - and its occupants - whole."--Amazon.
Created by Richard Ashley Hamilton
Ages 10+